Legislation improvement for the expulsion of foreigners and stateless persons from the Republic of Kazakhstan - Oleinik, V.I. (Bulletin of the Karaganda University “Law Series”, 2022)
The increase in the number of foreign citizens and stateless persons staying in Kazakhstan, as well as foreign legal entities operating in the territory of our country, was due to the following factors: the removal of administrative bans and restrictions on the entry of foreign citizens (immigrants) and stateless persons, the openness of the Kazakhstani economy to foreign legal entities, and the development of economic, political, and international relations. In this regard, issues related to the use of administrative levers and procedures in suppressing unfavorable migration phenomena would be particularly important. At the same time, expulsion must be genuinely applied to immigrants who have committed serious illegal violations and must be consistent with the norms of international law. In this article, the author considers actual problems of foreigners and stateless persons’ expulsion from the Republic of Kazakhstan in an administrative manner, within the framework of the Civil Procedure Code and compulsorily in criminal cases, taking into account the observance of human rights and international legal acts. The algorithm of interaction between the Migration Service Committee and the Committee on the Penal Correction System of the Ministry of Internal Affairs of Kazakhstan for the expulsion of immigrants is disclosed. The purpose of this article is to identify problems of legal regulation, eliminate gaps, and elaborate clear legal grounds for preventive restrictions on freedom of movement for the forced expulsion of foreigners and stateless persons from the country, as well as to improve legislation in this area. To sum up, the author concludes the novelties of the national legislation, which contributed to the settlement of problematic issues during the detention and forced expulsion of foreigners and stateless persons from the country, and justifies his position on the topic under consideration.